Specific leaf area is lower on ultramafic than on neighbouring non-ultramafic soils. (5th December 2022) - Samojedny, Thomas J.; Garnica-Díaz, Claudia; Grossenbacher, Dena L.; Adamidis, George C.; Dimitrakopoulos, Panayiotis G.; Siebert, Stefan J.; Spasojevic, Marko J.; Hulshof, Catherine M.; Rajakaruna, Nishanta
ABSTRACT: Background: Specific leaf area (SLA) is a core trait within the leaf economic spectrum that describes differences in plant performance and productivity. Research on the sources of variation in the leaf economic spectrum and SLA has primarily focused on climate. Much less is known about SLA variation across unusual edaphic environments, such as on ultramafic soils. Aims: To determine the role of ultramafic soils as a driver of SLA variation. Methods: We measured SLA for dominant species on paired ultramafic and non-ultramafic soils in five biogeographically distinct regions around the globe and compared mean SLA values to globally reported values. Results: SLA was lower on ultramafic than on non-ultramafic soils in all regions, except Puerto Rico, and both climate and soil were important drivers of SLA. For three of the five regions, SLA values on ultramafic soils were lower than the global average. Conclusions: Soils can be a major driver of SLA along with climate. Low SLA on ultramafic soil points to selection for stress resistance strategies. Furthermore, in some bioregions, SLA values on ultramafic soils were among the lowest on the planet and thus represent globally rare phenotypes that should be conserved within these unique edaphic habitats.